Membangun Jiwa Kreatifitas Pelaku UMKM Di Desa Jatisura, Cikedung, Indramayu, Jawa Barat - Widayani Wahyuningtyas; Kharisma Wati Gusti; Elthon Gabriel; Yonita Laty Aisyah; Ibnu Malkan Bakhrul Ilmi (IKRA-ITH ABDIMAS, 2023)
The role of Indonesia in realizing nationalism is that the Indonesian people fill it by being an active marketparticipant in global competition. For this reason, business actors are needed who have ideas that are realized increativity products. the goal of the service is how to open the behavior pattern of the local community to be productive,(Creating creative ideas into products that can compete in the business world. departing from the hope of the servantto be able to help UMKM business actors to improve their standard of living. The target that the servant wants toachieve is the actors Businesses can open patterns of behavior to be productive and their creative spirit grows amongUMKM business actors. Implementation Method, The population is all PKK mothers who are active in Jatisuravillage, while the sample is PKK mothers who are active in their business activities (Business Actor) 17 business actorparticipants In this service qualitative data collection, tools or instruments Media counseling and training of PKKwomen are active business actors In this service using descriptive quantitative methods, the results obtained are thatthe results of distributing pre and posttest questionnaires for village business actors Jatisura , Cikedung, Indraayutaken According to the pre test, the pre test results were 7.933 and the post-test was 8, 133, there was an increase inthe Creative Mindset Ability of business actors. Suggestions Village officials are expected to provide adequatefacilities and infrastructure to improve the villages of Jatisura, Cikedung, Indramayu.